Fluorescence microscopy-based quantitation of GLUT4 translocation. (1st April 2022) - Heckmann, Mara; Klanert, Gerald; Sandner, Georg; Lanzerstorfer, Peter; Auer, Manfred; Weghuber, Julian
Abstract: Postprandial insulin-stimulated glucose uptake into target tissue is crucial for the maintenance of normal blood glucose homeostasis. This step is rate-limited by the number of facilitative glucose transporters type 4 (GLUT4) present in the plasma membrane. Since insulin resistance and impaired GLUT4 translocation are associated with the development of metabolic disorders such as type 2 diabetes, this transporter has become an important target of antidiabetic drug research. The application of screening approaches that are based on the analysis of GLUT4 translocation to the plasma membrane to identify substances with insulinomimetic properties has gained global research interest in recent years. Here, we review methods that have been implemented to quantitate the translocation of GLUT4 to the plasma membrane. These methods can be broadly divided into two sections: microscopy-based technologies (e.g., immunoelectron, confocal or total internal reflection fluorescence microscopy) and biochemical and spectrometric approaches (e.g., membrane fractionation, photoaffinity labeling or flow cytometry). In this review, we discuss the most relevant approaches applied to GLUT4 thus far, highlighting the advantages and disadvantages of these approaches, and we provide a critical discussion and outlook into new methodological opportunities.